Hubungan Sanitasi, Personal Hygiene Dan Kandungan Escherichia Coli Dengan Diare Di Puskesmas Dinoyo Kota Malang - Rischa Dwitasari; Djoko Kustono; Muhammad Al-Irsyad; Marji Marji (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Diarrhea is the main cause of death globally. Diarrhea is a condition where liquid stools occur when defecating and the intensity is more than 3 times a day due to Escherichia coli infection. Factors that cause diarrhea are unsafe clean water facilities, water contamination by feces and poor personal hygiene habits. Diarrhea is included in the top 10 most common diseases in Malang City and the highest cases are in the Dinoyo Health Center area. The aim of the study was to identify the relationship between sanitation facilities, personal hygiene and E. coli content on the incidence of diarrhea. This type of research is cross-sectional quantitative with a purposive sampling method, totaling 35 samples. Data were analyzed by Chi-Square and multiple logistic regression tests. Bivariate test analysis resulted in a value of p=0.011 for sanitation facilities, p=0.007 for personal hygiene and p=0.000 for E. coli content. Meanwhile, the most influential variable is known, namely the content of E. coli in clean water (p=0.012) with a value of (OR=41.562; 95% CI 2.259-764.763). In conclusion, there is a relationship between sanitation facilities, personal hygiene and E. coli content with the incidence of diarrhea.